Implementasi Kebijakan Penataan Pedagang Kaki Lima Di Wilayah Museum Tugu Pahlawan Kota Surabaya (Studi Pada Dinas Koperasi Dan Umkm Kota Surabaya) - Rohman, M. Risky Ainur; Prathama, M.Si, Drs. Ananta (Institut Riset dan Pengembangan Indonesia, 2023)
Street vendors (PKL) in the Tugu Pahlawan area of Surabaya are still not well organized and managed, meaning that the local government must evaluate this in collaboration with related parties. Street vendors in the area along the Kedungdoro road, even though they are neatly arranged, still interfere with the highway traffic. In addition, street vendors (PKL) use the roadside to spread their wares, even though the roadside is made for pedestrians. With the use of the roadside for selling, pedestrians use part of the highway to walk; this is what makes traffic jams. This study aims to determine the implementation of the Surabaya City Regulation No. 9 of 2014 in structuring and providing space for street vendors in the city of Surabaya (Study on Street Vendors Along Jalan pahlawan Surabaya). Sampling using purposive sampling, namely the relevant local government authorities and street vendors (PKL). Qualitative descriptive analysis technique.